Appetite controlled by a cholecystokinin nucleus of the solitary tract to hypothalamus neurocircuit - D'Agostino, Giuseppe (eLife, 2016)
The nucleus of the solitary tract (NTS) is a key gateway for meal-related signals entering the brain from the periphery. However, the chemical mediators crucial to this process have not been fully elucidated. We reveal that a subset of NTS neurons containing cholecystokinin (CCK(NTS)) is responsive to nutritional state and that their activation reduces appetite and body weight in mice. Cell-specific anterograde tracing revealed that CCK(NTS) neurons provide a distinctive innervation of the paraventricular nucleus of the hypothalamus (PVH), with fibers and varicosities in close apposition to a subset of melanocortin-4 receptor (MC4R(PVH)) cells, which are also responsive to CCK. Optogenetic activation of CCK(NTS) axon terminals within the PVH reveal the satiating function of CCK(NTS) neurons to be mediated by a CCK(NTS)→PVH pathway that also encodes positive valence. These data identify the functional significance of CCK(NTS) neurons and reveal a sufficient and discrete NTS to hypothalamus circuit controlling appetite. DOI: http://dx.doi.org/10.7554/eLife.12225.001